Another Method of Integrated Teaching of Chemistry and Biology - Margalitashvili, Darejan; Davitashvili, Magda; Ghagholishvili, Mzia (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The article presents another example of integrated teaching of subjects. In particular, the integration of chemistry and biology in the educational process. The effectiveness of the integrated lesson is due to the fact that the student examines the issue in terms of different disciplines; establishes connections between subjects; At the same time, he/she considers the issue as a whole; Makes a transfer between subjects. Integrated lessons have a large functional role. For this purpose, it is important to highlight the integration within any study discipline defined by the national curriculum and integrated approaches to teaching the issue within different subjects. Integration between subjects allows students to study a specific issue not separately and fragmented, but to combine the knowledge gained in separate subjects and, based on the target concepts, imagine the interrelationship between subjects and events as a whole. The presented integrated lesson was conducted in the 11th grade. The topic of the lesson was food additives, during which the students naturally connected food with human health. After the end of the educational process, students' awareness about food additives increased. Responsibility for living a healthy lifestyle also increased. Students understood the importance of a healthy life, were able to record data, organize, process and present information in different forms. They understood and substantiated that the adopting a healthy lifestyle is important for human health.